2019
DOI: 10.11144/javeriana.upsy18-3.ccsa
|View full text |Cite
|
Sign up to set email alerts
|

Componentes cognitivos del sistema de aproximación numérica y la fluidez de cálculo en niños de educación primaria

Abstract: En los últimos años, se ha investigado la relación existente entre los dos sistemas cognitivos que contribuyen al procesamiento de cantidades (el sistema de aproximación numérica (SAN) y el (SEN) sistema de exactitud numérica) y su influencia en el rendimiento y dificultades de aprendizaje de las matemáticas. En este estudio, se investiga la relación entre la precisión del SAN y el rendimiento matemático en una prueba de fluidez de cálculo simbólico en alumnado de segundo y tercer ciclo de educación primaria (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
2
0
1
Order By: Relevance
“…These studies indicate a clear role of the Numerical Approximation System (NAS), a cognitive system that facilitates the manipulation and representation of information about numbers and quantities in an approximate manner, and is found not only in adults but also in infants and even in animals (Feigenson et al, 2013). These skills can be assessed through non-symbolic comparison tasks, such as that used in this study (Aguilar et al, 2019). In previous research, Rittle-Johnson et al ( 2017) have paid special attention to domain-specific factors and indicated their relevance to non-symbolic knowledge in early childhood education, as a predictor of later mathematical performance.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…These studies indicate a clear role of the Numerical Approximation System (NAS), a cognitive system that facilitates the manipulation and representation of information about numbers and quantities in an approximate manner, and is found not only in adults but also in infants and even in animals (Feigenson et al, 2013). These skills can be assessed through non-symbolic comparison tasks, such as that used in this study (Aguilar et al, 2019). In previous research, Rittle-Johnson et al ( 2017) have paid special attention to domain-specific factors and indicated their relevance to non-symbolic knowledge in early childhood education, as a predictor of later mathematical performance.…”
Section: Discussionmentioning
confidence: 84%
“…These studies indicate a clear role of the Numerical Approximation System (NAS), a cognitive system that facilitates the manipulation and representation of information about numbers and quantities in an approximate manner, and is found not only in adults but also in infants and even in animals (Feigenson et al, 2013). These skills can be assessed through non-symbolic comparison tasks, such as that used in this study (Aguilar et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Igualmente, al analizar las palabras clave utilizadas para determinar el alcance de los artículos, es posible identificar las tendencias y brechas de la investigación. Recientemente, las técnicas bibliométricas se han utilizado en la bibliografía para permitir una mejor comprensión del estado del arte en temas relacionados con la educación primaria, como: Cinco problemas en la formación de maestros y maestras para enseñar ciencias en Educación Primaria (De Pro et al, 2022), Componentes cognitivos del sistema de aproximación numérica y la fluidez de cálculo en niños de educación primaria (Aguilar Villagran et al, 2019), Educación sobre higiene alimentaria en las escuelas primarias del Reino Unido: una encuesta nacional sobre las opiniones de los profesores (Bielby et al, 2006), e Importancia de las actitudes hacia las personas con discapacidad en Educación Infantil y Primaria una Revisión sistemática (Hernández Beltrán et al, 2023). Por lo tanto, el objetivo de este artículo, es evaluar la cantidad de publicaciones que trata sobre la innovación de la enseñanza-aprendizaje en la educación primaria, para lograr comprender las tendencias de dicha investigación y los temas que han despertado el interés de los investigadores.…”
Section: Innovación De La Enseñanza Aprendizaje En La Educación Prima...unclassified